Application of the generalized Kudryashov method to the Eckhaus equation - Arnous, Ahmed H. H.; Mirzazadeh, Mohammad (Nonlinear Analysis: Modelling and Control, 2016)
In this paper, the generalized Kudryashov method is presented to seek exact solutions of the Eckhaus equation. From these solutions, we can derive solitary wave solutions as a special case. The proposed method is direct, effective and convenient and can be applied to many nonlinear evolution equations in mathematical physics.
Keywords: nonlinear evolution equations; exact solutions; Eckhaus equation; generalized Kudryashov method